Assessing the macroeconomic impact of extending hotel height limitations - Brian Micallef; Silvio Attard (Central Bank of Malta, 2015)
This paper presents estimates of the macroeconomic impact of the recently revised policy framework by the Malta Environment and Planning Authority (MEPA) to facilitate the vertical extension of hotels which are rated as three-star or above by the Malta Tourism Authority (MTA). The simulations are based on the Central Bank of Malta's structural econometric model described in Grech and Micallef.
Keywords: 330